Penggambaran Ornamen Ular Pada Arca Ganesha Koleksi Museum Candi Prambanan, Yogyakarta - Ashar Murdihastomo (Balai Arkeologi Yogyakarta, 2020)
Ganesha is the best-known deity after Trimurti in the Hindu pantheon. He is worshipped as the lord of beginnings and as the lord of removing obstacles. He is sculpted in various depictions. One of them, collected by the Prambanan Temple Museum, Yogyakarta, shows a snake and a mouse as his vahana (mount/vehicle). This image has never been found anywhere else. Therefore, this study was aimed to find out the mythological story behind that depiction and to investigate the past people’s understanding of it. This descriptive study employed an iconographic analysis to analyze the collected data. The analysis results indicate that Ganesha is revered as the protector of crop yield (the harvest deity).